Stabilisation of Laterite Soils With Cement and Metakaolin - Joel Agaba (Uganda Christian University, 2024)
The purpose of this research was to stabilize laterite soils using cement and metakaolin. The need for this research is driven from the problems experienced during cement stabilization particularly autogenous shrinkage that is associated with cement hydration. Metakaolin which is pozzolanic in nature has in previous research demonstrated the capacity to minimize this shrinkage by increasing the voids formed during hydration of cement. Metakaolin has also been found to improve the strength properties of concrete. Therefore, this research aimed at increasing the strength of laterite soil stabilized with cement and metakaolin. To achieve this, cement and metakaolin were mixed together with cement kept at a constant 3%, which is the optimum for this purpose according previous research and metakaolin increased from 0% to 8% in intervals of 2% in order to determine the suitable mix design for stabilization of the laterite soils. A design mix of 3% cement and 4% metakaolin was selected as the optimum since this soil gave the highest values for the strength properties of the laterite soil after stabilization that is 57% for CBR and 1.41MPa for UCS. The shrinkage characteristics of the soil that is PI, CBR swell and linear shrinkage were all found to be within the allowable range according to the MoWT general specifications for road and bridge works 2005.